Socio-Economic Factors on Women Empowerment - S. Indira, Dr. R. Karuppusamy, (International Journal of Scientific Research and Management (IJSRM), 2017)
This study focuses on the socio-economic factors on empowerment of women entrepreneurs in Puducherry region. The objective of the study is to analyze their socio-economic factors, to identify the reasons for which the women involve in entrepreneur activities. By using simple random sampling method for this study 250 sample respondents were interviewed with duly constructed schedule of questions. The result shows that demographic or socio-economic factors like community, nature of the family, educational qualifications, location of the business and building premises coordinate with women empowerment have impact on them. Statistical tool chi-square analysis was used for the findings of empowerment of women entrepreneurship in this study